High rate of self‐improving phenotypes in children with non‐syndromic congenital ichthyosis: case series from south‐western Germany. (29th July 2021) - Frommherz, L.; Krause, A.; Kopp, J.; Hotz, A.; Hübner, S.; Reimer‐Taschenbrecker, A.; Casetti, F.; Zirn, B.; Fischer, J.; Has, C.
Abstract: Background: Non‐syndromic congenital ichthyosis describes a heterogeneous group of hereditary skin disorders associated with erythroderma and scaling at birth. Although both severe and mild courses are known, the prediction of the natural history in clinical practice may be challenging. Objectives: To determine clinical course and genotype‐phenotype correlations in children affected by non‐syndromic congenital ichthyosis in a case series from south‐western Germany. Methods: We performed a retrospective observational study of 32 children affected by non‐syndromic congenital ichthyoses seen in our genodermatosis clinic between 2011 and 2020. Follow‐ups included assessment of weight and severity of skin involvement utilizing a modified Ichthyosis Area Severity Index (mIASI). mIASI was calculated as a sum comprising the previously published IASI score and an additional novel score to evaluate palmoplantar involvement. Linear regression was assessed using Pearson correlation, and statistical analysis was performed using the Wilcoxon–Mann–Whitney test. Results: This study included 23 patients with autosomal recessive congenital ichthyosis, seven with keratinopathic ichthyosis and two with harlequin ichthyosis. Cutaneous manifestations improved in more than 70% of the children during the follow‐up. Especially in patients with mutations in ALOXE3 and ALOX12B, mIASI scores dropped significantly. The most common phenotype observed in this study was designated ′mild fine scaling ichthyosis′. Severe palmoplantar involvement occurred in patients with KRT1 and ABCA12 mutations; most patients demonstrated hyperlinearity as a sign of dryness and scaling. Weight was mainly in the normal range and negatively correlated with the severity of skin involvement. Conclusions: Congenital ichthyosis that self‐improves and evolves with mild fine scaling ichthyosis was the most common phenotype observed in our patients. This type might be underdiagnosed if the genetic diagnosis is not performed in the first year of life. mIASI is an easy and fast instrument for scoring disease severity and adding additional points for palmoplantar involvement might be valuable.